2018
DOI: 10.19026/ajfst.14.5841
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the Composition of Coconut-Based Emulsions on the Stability of the Colloidal System

Abstract: The object of this research was to determine the influence of the composition of coconut milk-based emulsions on its physical and chemical stability. Coconut represents a highly important product globally and its competitiveness is restricted to its commercialization in the form of cakes, flour and coconut oil mainly to the European Community. The search for new alternatives to diversification of products as raw materials for food, pharmaceutical and cosmetic sectors represents a potential challenge. Coconut P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 60 publications
1
2
0
1
Order By: Relevance
“…Some researchers have reported that when a colloidal system presents a II> 25 mV, there is a strong electrostatic repulsion of the particles, which gives it an adequate physicochemical stability [18], [27], [29] Similar values have been reported for stable guacamole emulsions (II = 27,7 ± 0,3 mV) [51]. Other research has reported superior values in coconut-based colloidal systems (II = 45,6 ± 2,5 mV) [52] and in yacon (Smallanthus sonchifolius) suspensions (II = 33.8±4,0 mV) [27]; however, Marin et al, [53] reported stable blackberry suspensions with probiotics and prebiotics with II = 13.3 ± 0.3 mV. An increase of the amount of probiotic suspension with the addition of GA and xanthan gum is highlighted in some studies [27], [29], conferring greater stability to fruit pulps and their beverages.…”
Section: Characterization Of Strawberry-based Suspensionssupporting
confidence: 54%
See 1 more Smart Citation
“…Some researchers have reported that when a colloidal system presents a II> 25 mV, there is a strong electrostatic repulsion of the particles, which gives it an adequate physicochemical stability [18], [27], [29] Similar values have been reported for stable guacamole emulsions (II = 27,7 ± 0,3 mV) [51]. Other research has reported superior values in coconut-based colloidal systems (II = 45,6 ± 2,5 mV) [52] and in yacon (Smallanthus sonchifolius) suspensions (II = 33.8±4,0 mV) [27]; however, Marin et al, [53] reported stable blackberry suspensions with probiotics and prebiotics with II = 13.3 ± 0.3 mV. An increase of the amount of probiotic suspension with the addition of GA and xanthan gum is highlighted in some studies [27], [29], conferring greater stability to fruit pulps and their beverages.…”
Section: Characterization Of Strawberry-based Suspensionssupporting
confidence: 54%
“…La Xw presentó un comportamiento creciente en el tiempo, siendo en general mayor con el incremento de la T. El comportamiento de la aw fue correspondiente al de la Xw; sin embargo, estos comportamientos no fueron coherentes con respecto a la T, lo cual podría atribuirse a la heterogeneidad microestructural de los aglomerados, donde los puntos activos de las superficies de las MPAF no llegan a ser impregnados por la solución ligante de forma homogénea, unos aglomerados con respecto a otros, lo cual afecta los niveles de adsorción de agua durante el almacenamiento. En general, la Xw y aw son variables críticas, afectadas por T, t y T-t, cuyo comportamiento se considera como la resultante de dos fenómenos principalmente: 1) La interacción ambiente-empaque-MPAF a las condiciones del estudio, generó una fuerza motriz a favor de la adsorción de Xw en la MPAF, debido a la diferencia de potencial químico entre el interior de la cámara (aw: 0,650) y la superficie de la MPAF (aw < 0,361) (Lucas et al, 2018;Marulanda et al, 2018;Chang et al, 2018), y 2) Una mayor temperatura de almacenamiento genera una mayor presión parcial del agua en la superficie de la MPAF, lo cual contribuye a disminuir el contenido de Xw (Badui, 2006;Troller, 2012).…”
Section: Humedad Y Actividad Acuosaunclassified
“…The TS S presented a significant difference (p < .05) concerning TS BC and its quadratic interaction, where the mean values fluctuated between 8.6% and 10.6%, and the higher TS S content is consistent with the higher contribution of solids in the BC formulation, which is favorable in the spray dryer because it increases the production and energy performance (Lucas et al, 2018). Some researchers report that when fresh fruit is used, the higher TS S content is associated with a higher state of fruit maturity (Bernal et al, 2014).…”
Section: Suspensionsmentioning
confidence: 82%
“…In general, D 50 and D 90 behaved similarly, and this could be attributed to the resulting main phenomena: 1) weakening of the insoluble structure caused during the enzymatic hydrolysis process (Álvarez García, 2018), which confers a decrease in particle sizes; 2) saturation of enzymes on particle surfaces when the formulation contains high [Enzyme]. This second effect inhibited enzyme action without effectively reducing particle sizes and favoring attractive forces, which could confer aggregates and/or phase separations in CS CG (Carlos et al, 2018). Dahdouh et al (2018) stated that juices could be considered polydisperse suspensions that appear based on the predominant particle size.…”
Section: Design Of the Colloidal System Based On Cape Gooseberry Pulp...mentioning
confidence: 98%